Stability of Dynamical Systems Generated by Regularized Newton Method In Hilbert Spaces (Latakia University Journal -Basic Sciences Series, 2021)
Let  a real Hilbert space,  ,  are maximal monotones operators and  is locally Lipschitz continuous.The question is to find the zeroes of structured monotone operator  .In this article we  study the stability of Dynamical system in special situation when and  when  is convex, proper and lower-semi continuous,  is convex and differential.